2022
DOI: 10.1177/0044118x221126194
|View full text |Cite
|
Sign up to set email alerts
|

From Context to Perception to Behavior: Predicting Delinquency With the Parental Support-Perceived Parental Competence Cross-Lag

Abstract: The goal of this study was to determine the significance of variable order when it comes to using child and parent reports of parental support to predict delinquency. It was hypothesized that a social context variable (parental support as rated by the parent) would precede a perceptual variable (perceived parental support competence as rated by the child) in predicting delinquency, but a perceptual variable preceding social context would not. This hypothesis, based, in part, on social cognitive theory, was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…( 2022 ) note (drawing on Travers et al. ( 2012 )), having a “somewhat supportive” parent did not result in a more positive effect on the young person than if parents were in the “not at all supportive” category (Travers et al., 2012 ). Reflecting on the WHO’s definition of QoL (2012) (other than when it is unrelated to physical health), feeling fully supported by their parent(s) is key to TGD youth achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…( 2022 ) note (drawing on Travers et al. ( 2012 )), having a “somewhat supportive” parent did not result in a more positive effect on the young person than if parents were in the “not at all supportive” category (Travers et al., 2012 ). Reflecting on the WHO’s definition of QoL (2012) (other than when it is unrelated to physical health), feeling fully supported by their parent(s) is key to TGD youth achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…22 Risks for 2SLGBTQ+ youth can be reduced by family acceptance and connection with other 2SLGBTQ+ youth. 2225 In fact, lesbian, gay, bisexual and transgender (LGBT) youth who come from highly rejecting families are more than three times as likely to have attempted suicide than LGBT peers who reported no or low levels of family rejection. 24 In an Ontario-based study, a staggering 77 per cent of people who identified as transgender reported having seriously considered suicide at some time in their lives, 43 per cent reported attempting suicide at some point in their lives and 10 per cent reported attempting suicide in the past year.…”
Section: Discussionmentioning
confidence: 99%
“…One sequencing rule that is of cardinal significance in explaining crime and desistance states that social/environmental context variables normally precede cognitive (antisocial belief system), perceptual (perceived severity of punishment), and outcome (delinquency, crime) variables. Although this recently developed rule requires further investigation, Walters (2022a) uncovered preliminary evidence for its validity in a study in which parental support, as rated by the parents, preceded parental support, as perceived by the child, in predicting child delinquency. Reversing the sequence such that child-perceived parental support preceded parent-rated parental support failed to predict delinquency.…”
Section: Desistancementioning
confidence: 99%
“…Like the social context rule in which social context precedes perception/belief/outcome, the general flow of the developmental process over longer periods of time typically runs from perception to belief. In a study using a sample different from the one used in the Walters’ (2022a) investigation, Walters et al (2022) determined that child-perceived parental competence heralded changes in neutralization and cognitive impulsivity that, in turn, predicted youth delinquency. In contrast, neutralization and cognitive impulsivity followed by child-perceived parental competence failed to predict youth delinquency.…”
Section: Desistancementioning
confidence: 99%
See 1 more Smart Citation